The Impact of Cr(3+) Doping on Temperature Sensitivity Modulation in Cr(3+) Doped and Cr(3+), Nd(3+) Co-doped Y(3)Al(5)O(12), Y(3)Al(2)Ga(3)O(12), and Y(3)Ga(5)O(12) Nanothermometers - Elzbieciak, Karolina (Front Chem, 2018)
A new approach to enhance the sensitivity of transition metal ion based nanocrystalline luminescent thermometer is presented. It was shown that the increase of Cr(3+) concentration in three types of garnet host namely Y(3)Al(5)O(12), Y(3)Ga(5)O(12), and Y(3)Al(2)Ga(3)O(12) allows for significant enhancement of their performance in non-contact thermometry. This phenomenon is related to the weakening of the crystal field strength due to enlargement of average Cr(3+)-O(2−) distance at higher Cr(3+) concentrations. By increasing Cr(3+) concentration from 0.6 to 30%, the sensitivity increased by over one order of magnitude from S = 0.2%/°C to S = 2.2%/°C at 9°C in Y(3)Al(2)Ga(3)O(12) nanocrystals. Moreover, it was found that due to the Cr(3+) → Nd(3+) energy transfer in the Cr(3+), Nd(3+) co-doped system, the usable Cr(3+) concentration, for which its emission can be detected, is limited to 10% while the sensitivity at −50°C was doubled (from 1.3%/°C for Y(3)Al(2)Ga(3)O(12):10%Cr(3+) to 2.2%/°C Y(3)Al(2)Ga(3)O(12):10%Cr(3+), 1%Nd(3+) nanocrystals).